The effects of dietary fructose and salt on maternal, fetal and adult offspring growth, metabolic status and cardiovascular health - Gray, Clint (2011)
The modern Western diet is typically high in salt and fructose. Variations in maternal diet can have delayed developmental effects on the adult offspring’s cardiovascular function leading to acute or chronic hypertension. The aim of the work in this thesis was to determine the effect of moderate dietary salt and/or fructose intake on maternal and fetal growth, metabolic status and cardiovascular health of the adult offspring. Sprague Dawley rats were fed either 1) control diet (chow) with tap water, 2) salt diet, 4% NaCl, 3) fructose diet, purified chow plus 10% fructose in tap water or 4) fructose and salt diet for 28 days prior to conception, through gestation and lactation. Data were collected on the non-pregnant and pregnant dam, the fetus and neonate and the adult offspring. Cardiovascular data in adult offspring were recorded between the ages of 10-15 weeks by implanted radiotelemetry probes. Dams fed fructose prior to and during gestation increased caloric intake (P<0.001) from fructose water with a consequential decrease in total energy intake (P<0.001) from food. Increases in plasma glucose (P=0.04) (without an effect on insulin), triglyceride (P<0.014), non-esterified fatty acids (P<=0.05), cholesterol (P<0.001) and uric acid (P<0.004) were all increased by the consumption of fructose in pre-gestational females. Dams consuming salt prior to and during gestation elicited an increase in cardiac (P<0.001) and kidney tissue mass (P<0.001). Fructose-fed dams also displayed a significant redistribution of regional fat depots i.e. visceral fat increased (P<0.001) whilst gonadal fat decreased (P<0.008). Fructose also increased liver weight (P<0.001) and intra-hepatic triglyceride concentration was also observed to be increased (P<0.007). However, few effects on the fetus but subtle effects on fetal and neonatal growth were observed at this stage. Fructose and salt combined reduced litter size (7 vs. 14 pups) (P<0.001) without an effect on birth weight. Maternal fructose diet skewed the sex ratio in favour of males (60:40) (P<0.001) and maternal salt influenced placental architecture (decreased labyrinthine (P<0.007), increased trophoblast layer (P=0.03)) and had marked effects on maternal osmolality (P<0.001). Male (P=0.07) and female (P<0.02) offspring from fructose-fed mothers had relatively heavier livers. In the adult offspring male and female offspring plasma osmolality was significantly increased in offspring fed prenatal salt (P<0.001). In the offspring, maternal salt diet significantly increased (~15mmHg) basal mean arterial pressure (MAP) in the adult male offspring (P<0.001), but significantly decreased basal MAP (~8mmHg) in the adult female offspring. Both fructose and salt diet had effects on the circadian variation in blood pressure and heart rate. Subsequent cardiovascular challenges revealed little beyond an altered cardiovascular set-point in these offspring. The study emphasizes the importance of quality rather than quantity when assessing maternal diet, particularly in terms of its mineral and simple sugar content. In conclusion, data within this thesis demonstrates for the first time a moderate maternal dietary intake of salt and fructose can affect offspring osmolality profile and blood pressure in a sex-specific manner and produce a pattern of symptoms resembling NAFLD which, in part, are passed vertically to the offspring.